Capital structure of Portuguese hotel firms: a structural equation modelling approach - Fernanda Matias; Leonor Salsa; Carlos Miguel Afonso (Tourism & Management Studies)
This paper addresses capital structure determinants for Portuguese hotel firms between 2006 and 2014. Secondary data from 356 hotel units was analysed using the partial least squares (PLS) statistical technique, a variance-based structural equation modelling (SEM). The results show that the explanatory variables proposed as capital structure determinants have an impact on the financing and debt decisions made by the firms in the sample. Of these, tangibility has the greater explanatory power. Overall, the results support the notion that trade-off theory and pecking-order theory are important in explaining the capital structure of the Portuguese hotel industry, particularly as regards the agency conflicts triggered by growth opportunities and the preference firms have for internal funding. The results also point to the importance of collateral in accessing credit and the lesser impact of asymmetric information pertaining to tangible asset value and firm size. The results suggest small firms find it difficult to contract loans, which can somewhat limit their growth and performance.